Kajian Strategi Bersaing Ritel Tradisional di Kota Payakumbuh - Alfikri Alfikri; Silfia Silfia; Darnetti Darnetti; Nelvia Iryani (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
Payakumbuh City is inhabited by 141,184 people, most of whom have a labor force participation rate of 71.73 percent, most of whom work in the trade sector, especially traditional retail. However, the increasingly rapid development of modern retail means that traditional retail is starting to be abandoned by consumers, so according to researchers there must be a competitive strategy. needed to help traditional retail survive. The methods in this research are 1). Identification stage evaluation of internal factors, evaluation of external factors, 2). Matching stage with Internal-External Matrix, SWOT, and 3). Conclusion stage with SQPM. The research results can explain that the internal and external conditions of traditional retail in Payakumbuh City are quite good because the total EFI value is 2.89 and EFE is 3.2. This is in quadrant II on the IE matrix with a general strategy of growth and development, on the SWOT matrix it gets 7 Alternative strategies were then ranked by the seven strategies using the QSPM matrix, so the highest score was in strategy 1, namely providing comfortable shopping services for motorists with free and safe parking with a score of 5.12 and strategy 2, providing neater product displays, price labeling with better lighting. enough with a score of 4.87.